The Omnipresence of Cancer: Two Perspectives. (July 2020) - Zumstein-Shaha, Maya; Lynn Cox, Carol; Fawcett, Jacqueline
Abstract : This article aimed at describing the development of a theory of the experience of living with cancer. Secondary analysis of data from a series of studies yielded the concepts and propositions of the theory of the omnipresence of cancer. Theory construction was guided by Heidegger's ontology of dasein, whereas Newman's grand theory of health as expanding consciousness guided theory evolution. The theory includes 4 concepts—influencing factors, toward authentic dasein, mapping out the future, and living with cancer—each of which has several dimensions. Based on this theory, nursing interventions can be developed and tested to support persons with cancer.